The Continuing Relevance of Marxism for Popular Education Today (Concept: The Journal of Contemporary Community Education Practice Theory, 2019)
This contribution argues that Marxism is more relevant than ever, and particularly so for popular education and development in the contemporary context. The first section summarises the major challenges to be faced, with the growth of far-right populism on a global scale.  How are we to make sense of these developments? And how should we respond, in developing community-based strategies for social justice and social solidarity? These questions set the context for identifying the relevance of key features of Marx’s approach, focussing on his analysis of class, class consciousness and class conflict, as capitalism expands across the globe. Armed with these analytical tools, community and youth workers and popular educators have the equipment to support communities in challenging the growth of far-right populism, contributing to the development of more progressive agendas for social change. There are alternatives to neo-liberal agendas, just as there are alternatives to their effects, including the alienation and the anger that populist politicians foster, for reasons of their own. Marxism provides no easy answers, but it does provide the analytical tools with which to develop such alternatives from the bottom up.